Development of VLAB-CHEM for form four student based on constructivism-cognitivism-contectual approach - Bakar, Norasiken; Badioze Zaman, Halimah; Shahbodin, Faaizah (Institue of Technology Management and Entrepreneurship, Universiti Teknikal Malaysia Melaka (UTeM), 2007)
This paper is about the development of a virtual laboratory for the subject of chemistry in Malaysian secondary schools (VLab-Chem). in this research, the term virtual laboratory is used to demonstrate to the student that although they are not physically in a laboratory conducting an actual experiment, the VLab-Chem helps them to accomplish an experiment through computer interaction. Students have the capacity to utilize the materials and apparatus often used in experiments and see the complete reaction of the experiment through animation and simulation. The discussion involves the modelling of the theoritical framework where it divides into three parts which are analysis and design, development and evaluation. For the second objectives, the researchers view on the constructivism-cognitivism-contextual lifecycle model. for the third objectives, the researcher explain the laboratory architecture of development VLab-Chem. while designing the development of VLab-Chem, the researchers have used an approach in learning theory which is the constructivism-cognitivism-contextual theory which is concept hrough learning-by-doing, contextual education, simulation, animation to create virtual based on learning, added in the VLab-Chem.